TINJAUAN FIKIH EKONOMI TERHADAP PRAKTIK JOKI GAME ONLINE PLAYER UNKNOWN BATTLE GROUND (STUDI KASUS DI DESA PANYABUNGAN III KECAMATAN PANYABUNGAN KABUPATEN MANDAILING NATAL - Muhammad Yasir Nasution; Zainuddin (Program Studi Ekonomi Syariah Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2022)
This article examines the economic fiqh review of the practice of online game jockey player unknown battle ground (PUBG) in Panyabungan III Village, Panyabungan District, Mandailing Natal Regency. The problem is how the legal practice of jockey games online player unknown battle ground (PUBG) in Panyabungan III Village, Panyabungan District, Mandailing Natal Regency. The type of research used is a qualitative approach field research. The source of the data in this study was obtained from interviews with online game jockey players unknown battle ground (PUBG) in Panyabungan III Village, Panyabungan District, Mandailing Natal Regency. The data is processed by analyzing the phenomenon and associated with the study of Islamic economic jurisprudence. The results obtained are in the perspective of economic fiqh, the practice of jockey games online player unknown battle ground (PUBG) in Panyabungan III Village, Panyabungan District, Mandailing Natal Regency using a lease agreement (ijarah) using the services of samsarah. Using the services of a jockey client will feel a loss for himself because his game account will not provide much benefit for him as well as only raising the Tier on his account is just a pleasure, actually in Islam this is an excessive and wasteful act. So it can be concluded that the PUBG Online Game Jockey in Panyabungan III Village, Panyabungan District, Mandailing Natal Regency is haram because it does not meet the pillars and conditions such as containing immoral and haram elements.